ANALYSIS OF INCOME INEQUALITY IN JAVA ISLAND AND ITS INFLUENCING FACTORS IN 2012-2023 - Diah Tri Agustina (MediaTrend, 2025)
This study aims to analyze the effect of Economic Growth (GRDP), Human Development Index (HDI), and Unemployment on Income Inequality in Java during the period 2012-2023. The data used in this study are secondary data obtained from the Central Bureau of Statistics (BPS). This research uses panel data regression model with Random Effect Model (REM) approach and analyzed using Eviews12 software. The regression analysis results show that partially the variables of Economic Growth, HDI, and Unemployment have a positive and significant effect on income inequality in Java Island in 2012-2023. The simultaneous test results show that the variables of economic growth, HDI, and Unemployment have a positive and significant influence on income inequality in Java Island in 2012-2023. From the results of this study, it is expected that the government can provide appropriate policies so that the policies implemented can be realized and the government is also expected to be able to create jobs, improve the quality of education and training to reduce the level of income inequality.